Matrine induces senescence of human glioblastoma cells through suppression of the IGF1/PI3K/AKT/p27 signaling pathway - Wenjing Zhou; Jiwei Wang; Qichao Qi; Zichao Feng; Bin Huang; Anjing Chen; Di Zhang; Wenjie Li; Qing Zhang; Rolf Bjerkvig; Xingang Li; Jian Wang (Cancer Medicine)
Abstract Background Matrine, a traditional Chinese medicine, has recently been shown to have antitumor properties in diverse cancer cells. Here, we explored the effect of matrine on human glioblastoma multiforme (GBM) cells. Methods Glioblastoma multiforme cell lines were treated with matrine to assess proliferation and viability using EdU and CCK8 assays. SA‐β‐gal assays were used to evaluate cellular senescence, and a cytokine array and ELISA assay were used to screen for secreted cytokines altered in GBM cells after matrine treatment. Immunohistochemistry and Western blot analysis were performed to evaluate protein levels in matrine‐treated cell lines and in samples obtained from orthotopic xenografts. Specific activators of AKT and IGF1 were used to identify the pathways mediating the effect. Results Matrine potently inhibited growth of GBM cell lines in vitro. Based on in situ assays, growth arrest induced by matrine was primarily achieved through induction of cellular senescence. Matrine treatment led to decreased expression of proteins involved in promoting cell growth, IGF1, PI3K, and pAKT. Exposure of cells to a small molecule activating AKT (SC79) and recombinant IGF1 led to a reduced number of senescent SA‐β‐gal‐positive cells in the presence of matrine. Finally, matrine inhibited growth of orthotopic xenografts established from luciferase‐stable‐U251 or luciferase‐stable‐P3 cells and prolonged overall survival in mice. Conclusions These results indicated that matrine arrested cell growth through inhibition of IGF1/PI3K/AKT signaling. Matrine warrants further investigation as a potential therapy in the treatment of patients with GBM.